Free Flap Selection and Outcomes of Soft Tissue Reconstruction Following Resection of Intra-oral Malignancy - Young, Adam M. H. (Front Surg, 2019)
Introduction: Surgery to resect intra-oral malignancy is a well-established mode of primary treatment. The tissue requirement in this area is for a thin, pliable flap with minimal bulk and this has historically been provided by free tissue transfer with a radial forearm free flap (RFFF). More recently, a role for the anterolateral thigh free flap (ALTFF) has been described, although in populations with a westernized diet, body habitus may preclude use of an ALTFF due to flap thickness, relative to a radial forearm free flap. Methods: An analysis of data was performed retrospectively for 90 consecutive patients with intra-oral malignancy, requiring immediate soft tissue reconstruction by the senior author, at Addenbrooke's Hospital between July 2008 and April 2016. Cases requiring bony reconstruction were excluded. Data on patient age, sex, indication for surgery, tumor location and defect type, complications, success rates, and length of stay were recorded. Results: The majority of patients received an ALTFF (n = 56) with 38% receiving a RFFF (n = 34). Surgical resection took place in the floor of the mouth most frequently. These were closed with ALTFF and RFFF in 41 and 28 occasions, respectively. A success rate of 97% was observed in the RFFF group; 1 flap developed partial necrosis and required complete revision. In the ALTFF group, there was a 100% flap success rate. ALTFF usage resulted in a reduction in the number of intraoperative (p = 0.021) in addition a reduction in the number of days in ITU (p = 0.01) and post-operative clinic visits (p = 0.025). Conclusion: We present a series that used predominately the ALTFF to reconstruct intra-oral defects following resection of squamous cell carcinoma in a Western population. The results demonstrate that this treatment can produce at least as comparable results as to the use of a RFFF repair in this population, whilst avoiding the donor site morbidity and aesthetic compromise of a RFFF.